(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Liudmila Sergiivna was one of the best pupils of Acad. V.P. Filatov and Acad. N.O. Puchkovska. Throughout her life, she tried to develop further and promote the ideas and knowledge she had gained from her teachers, and to instill the basics of the Filatov’s ophthalmological school in her young colleagues. She used to repeat the Acad. Filatov’s words “the path of science is thorny, but there is nothing better than science and truth”, and even the most hopeless patient should be cared for to have him or her “see the light in all its beauty of various colors and forms”.